Evaluating the shading effect of photovoltaic panels to optimize the performance ratio of a solar power system - Jamal Jamal; Ilyas Mansur; Adam Rasid; Musrady Mulyadi; Muhammad Dihyah Marwan; Marwan Marwan (Results in Engineering, 2024)
The objective of this research is to examine the problems of the shading effect of photovoltaic (PV) systems. This research describes the PV system installed on the rooftop of the administration building at Polytechnic State of Ujung Pandang-Makassar, Indonesia (called PNUP). To achieve the proposed method, the PVsyst application was applied to evaluate the shading effect, loss diagram and performance ratio (PR) over the entire year using the PVsyst software. The proposed scheme also examines the financial analysis of the proposed PV system, namely: payback period (PBP) and return of investment (ROI). Four perspective designs of photo voltaic-filled with different tilts and azimuth were selected. Research results indicated that the PR of designs_1, 2, 3 and 4 were: 0.816, 0.816, 0.817 and 0.815. The energy losses for all designs were: 11.40 MWh (design_1); 11.38 MWh (design_2); 11.67 MWh (design_3) and 11.04 MWh (design_4). In addition, the financial analysis was investigated to define PBP and ROI. The PBP and ROI for designs_1, 2, 3 and 4 were: 8.2 years with 145.2 % return rate; 8.2 years with 144.3% return rate; 7.8 years with 155.2 % return rate and 8.6 years with 131.8% return rate.